Ovarian Actions of Estrogen Receptor-β: An Update - Drummond, Ann E.; Fuller, Peter J. (Seminars in Reproductive Medicine, 2012)
Estrogen is essential for folliculogenesis with independent roles attributed to each of the two estrogen receptors (ERs). ERβ, expressed predominantly by the ovarian granulosa cells, is required for antrum formation, preovulatory follicle maturation, expression of genes involved in ovarian differentiation (luteinizing hormone, aromatase, etc.), and follicle rupture during ovulation. Ovulatory dysfunction is associated with polymorphisms of the ERβ gene, and endocrine disruptors that selectively activate ERβ cause reproductive dysfunction and impairment fertility. ERβ may also exhibit antitumorigenic properties, with a decline in ERβ levels in epithelial ovarian cancers associated with more severe disease and poor prognosis. In this review, we examine the models that have been used to elucidate the roles ERβ plays in the ovary and consider the clinical consequences of altered ERβ expression or inappropriate activation of ERβ signaling.
Keywords: ovary; estrogen; estrogen receptor; cancer; environmental estrogens